The Learning Collaboratory: developing and evaluating public health students' skills while promoting community health - Viviana E. Horigian; Tatiana Perrino; Julie Kornfeld; Renae D. Schmidt; Sophia T. Gonzalez (Frontiers Media S.A., 2023)
IntroductionComplex and continuous developments in health and healthcare require innovative changes in programs that educate public health scientists and professionals. Public health change agents need critical competencies to confront today and tomorrow's leading problems including leadership, communication, interprofessional practice, and systems thinking.The context: challenges in public health educationPublic Health training programs teach competencies through their applied field experience and culminating project, typically late in the program, and often implemented in isolation from peers and faculty. Objectives and skills do not always align closely with community-based program needs. Students pursuing a degree in science in public health need to deeply comprehend multi-dimensional and interconnected systemic problems and communicate with diverse stakeholders across disciplines to produce relevant community-engaged research. The University of Miami Public Health Learning Collaboratory (LC) was established to transform the learning experience of public health master's students by providing opportunities to develop necessary core skills for effective public health practice early in their training, while applying these skills to address real-world public health needs in the community.The Learning Collaboratory: structure, pedagogical approach and programmatic detailsSpanning an average of 3 semesters, the LC promotes student involvement in collaborative and impactful capstone and thesis projects. Practice-based teaching and service learning are central approaches to teaching cross-cutting competencies of leadership, communication, problem solving, collaboration, and systems thinking in public health. Significant to the approach is the engagement of previous cohorts of senior students to teach back to junior students, further integrating concepts learned. Long term alumni feedback recognized strengths of the program, including its structure, teamwork & collaboration, critical thinking & problem solving, guidance, nurture & support, teaching back, and content & curriculum. Community partners agreed the LC prepared students to practice in the field of public health.DiscussionThe LC is a promising model for master's level public health education and community application, given the opportunities it provides to strengthen and integrate students' public health skills in a supportive environment, and enhance the transferability and sustainability of student and faculty's community public health work.